2000
DOI: 10.1128/jvi.74.24.11472-11478.2000
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Hepadnavirus Nucleocapsids Are Selected for Secretion by Envelope Protein-Independent Membrane Binding

Abstract: Hepadnaviruses are DNA viruses but, as pararetroviruses, their morphogenesis initiates with the encapsidation of an RNA pregenome, and these viruses have therefore evolved mechanisms to exclude nucleocapsids that contain incompletely matured genomes from participating in budding and secretion. We provide here evidence that binding of hepadnavirus core particles from the cytosol to their target membranes is a distinct step in morphogenesis, discriminating among different populations of intracellular capsids. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
1
32
1
Order By: Relevance
“…This is consistent with previously published flotation experiments, which showed that only mature nucleocapsids have the intrinsic affinity and ability to interact with intracellular membranes. 32 We provide ultrastructural evidence that electron-dense nucleocapsids dock to the membrane of VCVs, leading to its deformation in the sense of an extrusion into the vesicle lumen (Fig. 4F).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previously published flotation experiments, which showed that only mature nucleocapsids have the intrinsic affinity and ability to interact with intracellular membranes. 32 We provide ultrastructural evidence that electron-dense nucleocapsids dock to the membrane of VCVs, leading to its deformation in the sense of an extrusion into the vesicle lumen (Fig. 4F).…”
Section: Discussionmentioning
confidence: 99%
“…32 Figure 4E shows particles of different densities measuring 22 to 27 nm in diameter in the cytosol (Fig. 4E, arrowheads).…”
Section: Ultrastructural Features Of the Early Steps Of Dhb Viral Budmentioning
confidence: 99%
“…These mechanisms would also apply to progeny capsids that are redirected to the nucleus for cccDNA amplification. How newly formed DHBV capsids are directed to the secretory pathway remains to be elucidated, however, since Mabit and Schaller (13) have shown that dephosphorylation alone is not sufficient to confer membrane affinity. The suggested model is in line with the previous observation in the duck model that serum-derived nucleocapsids are non-phosphorylated whereas nucleocapsids from liver tissue are highly phosphorylated (14).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear translocation of viral rcDNA is also mediated by incoming capsids in newly infected cells. However, the precise mechanisms regulating capsid trafficking and uncoating in both settings are unknown.Earlier studies in the DHBV model have shown that capsids from infected livers are highly phosphorylated while serumderived capsids and particles secreted from cultured cells are dephosphorylated (13,14). Furthermore, binding of in vitro generated HBV capsids to the nucleus of digitonin-permeabilized hepatoma cells was previously found to depend on the phosphorylation status of the core protein (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation